2010
DOI: 10.3354/meps08342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morphodynamic and estuarine gradients on the demography and distribution of a sandy beach mole crab: implications for source–sink habitat dynamics

Abstract: Several conceptual models relating biological and morphodynamic variables have been developed in sandy beach ecology. On estuarine sandy beaches, a major environmental factor influencing macrofaunal distribution is salinity. In this setting, the concurrent role of large-scale estuarine and morphodynamic gradients in shaping demographic patterns is still uncertain. To explain largescale variations in demographic aspects of the mole crab Emerita brasiliensis, 16 Uruguayan sandy beaches distributed along the estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 40 publications
3
27
0
5
Order By: Relevance
“…Annual length frequency distributions (LFDs) of the yellow clam population were grouped into 4 mm size classes. The index of recurrence of size classes (IRSC; Celentano et al 2010) was calculated as IRSC = N y /N t where N y defines the number (N) of size classes in a given year (y) and N t is the total number of size classes of Mesodesma mactroides observed in all years analyzed. IRSC ranges between 0 and 1 (all size classes present).…”
Section: Sampling Design Laboratory and Data Analysesmentioning
confidence: 99%
“…Annual length frequency distributions (LFDs) of the yellow clam population were grouped into 4 mm size classes. The index of recurrence of size classes (IRSC; Celentano et al 2010) was calculated as IRSC = N y /N t where N y defines the number (N) of size classes in a given year (y) and N t is the total number of size classes of Mesodesma mactroides observed in all years analyzed. IRSC ranges between 0 and 1 (all size classes present).…”
Section: Sampling Design Laboratory and Data Analysesmentioning
confidence: 99%
“…swash features, mean grain size, and wave height) and estuarine (e.g. salinity) gradients in aggregate population descriptors of macrofauna, such as abundance, biomass, recruitment, and body size (Celentano et al 2010;Lozoya et al 2010). Lozoya et al (2010) observed higher abundances of the isopod Excirolana armata for high salinities and intermediate ⁄ dissipative beaches with fine sands (<0.20 mm) and low organic matter (<0.1%).…”
Section: Discussionmentioning
confidence: 97%
“…swash features, mean grain size, and wave height) and estuarine ( e.g. salinity) gradients in aggregate population descriptors of macrofauna, such as abundance, biomass, recruitment, and body size (Celentano et al. 2010; Lozoya et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species with indirect development decreased at intermediate salinities, highlighting the sensitivity of these species to osmotic stress [22]. These species, characterized by free living larval stages, are exposed to changing environmental conditions throughout its life cycle, being particularly susceptible at early development stages [55].…”
Section: Discussionmentioning
confidence: 99%